Bleeding from gums: Can it be a dengue - Rajat Bansal; Purnita Goyel; Dinesh C Agarwal (Wolters Kluwer Medknow Publications, 2014)
Introduction: Bleeding from gums is a common feature in periodontitis patient. But abnormal bleeding from the gingiva or other areas of the oral mucosa that is difficult to control is an important clinical sign suggesting a hematological disorder. Case Report: A-40-year old male patient reported to our clinic with the chief complaint of acute gingival bleeding. There was continuous bleeding, fever since 3-4 days with weakness, retro orbital pain, and severe backache. Patient gave a history of bleeding from gums for last 24 hrs. His blood profile revealed; platelet count of 36,000, total wite blood cell (WBC) count of 6000/cumm, differential leukocyte count (DLC) (P45, L53, E2), and hemoglobin 12 g/dL. Patient sera was positive for dengue non-structural protein-1 antigen, anti-dengue immunoglobulin M (IgM), and anti-dengue immunoglobulin G (IgG) antibodies. Discussion: Here is a case report capable of changing our vision that acute gingival bleeding can also occur in dengue fever. Dengue fever can also be considered as one of the differential diagnosis for the acute gingival bleeding.